2021
DOI: 10.3390/s21010270
|View full text |Cite
|
Sign up to set email alerts
|

Gait Analysis under Spatial Navigation Task in Elderly People—A Pilot Study

Abstract: A decline in the Spatial Navigation (SN) abilities has been observed in the course of healthy aging. Walking is an inseparable part of the navigation process; however, research tasks overlook this aspect in studies involving seniors. The present study was designed to overcome this limitation by recording gait parameters during natural environment navigation and to determine gait indicators that most accurately assign the participants to the proper age category. Thirteen elderly (mean age = 69.1 ± 5.4 year) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Furthermore, we also anticipate that significant physiological parameters modifications (particularly, respiratory function) may be particularly associated with MsH, given that anxiety rather than depression significantly influences SN abilities in non-demented elders [92]. Starting from difficulties in spatial orientation evaluated in naturalistic experiments able to modify gait [93], we finally assume that patients with MCI due to AD will perform worse than SCD and healthy controls in terms of "Time" and "Speed", and report significant differences in "Direction", all variables collected by the Howdy Aptive app in the open-space naturalistic task.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also anticipate that significant physiological parameters modifications (particularly, respiratory function) may be particularly associated with MsH, given that anxiety rather than depression significantly influences SN abilities in non-demented elders [92]. Starting from difficulties in spatial orientation evaluated in naturalistic experiments able to modify gait [93], we finally assume that patients with MCI due to AD will perform worse than SCD and healthy controls in terms of "Time" and "Speed", and report significant differences in "Direction", all variables collected by the Howdy Aptive app in the open-space naturalistic task.…”
Section: Discussionmentioning
confidence: 99%
“…Then, other indicators can also be measured to characterize senescence. For human, we can detect the strength of muscle by grip strength test [ 56 ] and distinguish the young and senescent adults by gait indicators [ 57 ]. And other physiological measures such as heart rate and blood pressure are also related to senescence, in addition, brain, kidney, cardiovascular, and bone play roles in predicting senescence, and these indicators need to be considered together normally [ 58 ].…”
Section: Overview Of Senescencementioning
confidence: 99%
“…So it is a basis for assessing motor activity and anxiety behavior in mice [ 67 ] by the open field test [ 68 ] to determine the degree of senescence. Moreover, spatial, cognitive, and memory abilities are also important indicators of senescence [ 57 , 69 71 ], which can be assessed by fear conditioning [ 72 ], Y or T maze [ 63 ], the Barnes maze test [ 68 , 73 ], and Morris water maze experiment [ 72 ]. In addition to assessing aging based on the physiological characteristics described above, the status of aging can also be measured based on histological characteristics and biomarkers of aging.…”
Section: Overview Of Senescencementioning
confidence: 99%
“…One previous study found that navigational performance results were comparable between a VR and a real-world navigational test in young and older cognitively normal adults and people with dementia ( Cushman et al, 2008 ), but VR testing alone obviously does not allow assessment of gait and motion features during spatial navigation. On the other hand, several studies used wearable sensors to assess the gait and movement characteristics of cognitively normal older people and people with dementia in real-life situations ( Becu et al, 2020 ; Mc Ardle et al, 2021 ; Pawlaczyk et al, 2021 ; Weizman et al, 2021 ). Some of these real-world studies were primarily aimed at exploring different components of spatial orientation in normal human behavior and the underlying neural basis but did not aim to map the full range of navigational behavior in everyday situations ( Wei et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%